La Competencias investigativas en estudiantes de Educación Superior - Percial Carranza, Cristian Alonso (2025)
This study is part of a systematic review of research competencies in Higher Education students. The objective of the study is to analyze the existing scientific production on research competencies in Higher Education students during the last five years. In its methodology, the qualitative approach was considered, interpretive paradigm, documentary type, with a systematic review design and analytical descriptive scope. For this, electronic documents from indexed databases such as Scopus, Latindex and SciELO were used, also considering the Boolean operators “And, Or, Not”. A sample of 10 full-text and original articles, written in English and Spanish, was selected; which were analyzed to obtain relevant information. It was concluded that, of the ten scientific productions analyzed, the importance of developing research skills in higher education students is emphasized and the need to cultivate these skills from the first stages of academic training is highlighted.